Antenatal weight management: Diet, physical activity, and gestational weight gain in early pregnancy. (June 2017) - Swift, Judy A.; Langley-Evans, Simon C.; Pearce, Jo; Jethwa, Preeti H.; Taylor, Moira A.; Avery, Amanda; Ellis, Sarah; McMullen, Sarah; Elliott-Sale, Kirsty J.
Abstract: Objective: to investigate women's physical activity levels, diet and gestational weight gain, and their experiences and motivations of behavior change. Design: analysis of cross-sectional data collected during a longitudinal, cohort study examining physiological, psychological, sociodemographic, and self-reported behavioural measures relating to bodyweight. Setting: women recruited from routine antenatal clinics at the Nottingham University Hospitals NHS Trust. Participants: 193 women ≤27 weeks gestation and aged 18 years or over. Measurements & findings: measurements included weight and height, the Dietary Instrument for Nutrition Education (Brief Version), the International Physical Activity Questionnaire (Short Form), and open questions of perceptions of behaviour change. 50.3% (n=97) were overweight/obese, and women gained 0.26 kg/wk (IQR 0.34 kg/wk) since conception. The majority consumed low levels of fat ( n =121; 63.4%), high levels of unsaturated fat ( n =103; 53.9%), and used a dietary supplement ( n =166; 86.5%). However, 41% ( n =76) were inactive, 74.8% ( n =143) did not consume high levels of fibre, and 90.0% ( n =171) consumed less than 5 portions of fruit and vegetables a day. Body mass index category was not associated with diet, physical activity levels, or gestational weight gain. Themes generated from open-questions relating to behaviour change were: (1) Risk management, (2) Coping with symptoms, (3) Self-control, (4) Deviation from norm, (5) Nature knows best. Conclusions: early pregnancy is a period of significant and heterogeneous behaviour change, influenced by perceptions of risk and women's lived experience. Behaviour was influenced not only by perceptions of immediate risk to the fetus, but also by the women's lived experience of being pregnant. Implications for practice: There are exciting opportunities to constructively reframe health promotion advice relating to physical activity and diet in light of women's priorities. The need for individualized advice is highlighted, and women across all body mass index categories would benefit from improved diet and physical activity levels. Highlights: Women experience strong physical cues in relation to diet and physical activity. Areas of concern are; intakes of fibre, fruit and vegetables and physical activity. Behaviour change related to women's lived experience of pregnancy. Person-centred approach could embrace the subjective nature of pregnancy symptoms. Unprejudiced, tailored advice about weight-related pregnancy behaviours is needed.